Pembatasan Kewenangan DPR dalam Seleksi Jabatan Publik di Bidang Kekuasaan Eksekutif - Yani, Ahmad; Julhijah, Ratu (Pusat Analisis Keparlemenan Badan Keahlian Setjen DPR RI, 2023)
The authority of the House of Representatives (DPR) in the selection of public officials in the executive branch has been expanded after the amendments of the 1945 Constitution of the Republic of Indonesia. This research aims to evaluate the constitutionality of the DPR’s authority in the selection of public officials in the executive branch and map out the purification of this authority. This research utilizes normative research methods with statutory, conceptual, and historical approaches. The research results indicate that there are problems with the laws and regulations governing the selection of public officials, such as the Chief of the National Police, the TNI Commander, and the Head of the Nusantara Authority. This authority was originally vested in the President and cannot be interpreted as applying the principle of checks and balances. The DPR’s involvement in this matter has resulted in the overpowering of the DPR, the politicization of public officials, and the disruption of executive power stability in a presidential system. The purification of the authority to select public officials in the executive branch can be achieved by removing provisions in the law that involve the DPR in filling public positions in the executive branch. In the selection of public officials in the executive branch, the control that can be exercised is to involve substantial public participation in responding to candidates for public officials. AbstrakKewenangan Dewan Perwakilan Rakyat (DPR) dalam seleksi pejabat publik di bidang eksekutif diperluas pascaamandemen Undang-Undang Dasar Tahun 1945. Penelitian ini bertujuan untuk mengevaluasi konstitusionalitas kewenangan DPR dalam seleksi jabatan publik di bidang eksekutif dan memetakan purifikasi kewenangan tersebut. Kajian ini menggunakan metode penelitian normatif dengan pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan historis. Hasil penelitian menunjukkan adanya permasalahan dalam peraturan perundangundangan yang mengatur seleksi lembaga publik, seperti Kapolri, Panglima TNI, dan Kepala Otorita Ibu Kota Nusantara. Seharusnya, kewenangan tersebut menjadi kewenangan asli Presiden dan tidak dapat dimaknai sebagai penerapan prinsip check and balance. Keterlibatan DPR dalam hal ini mengakibatkan over power yang dimiliki oleh DPR, praktik politisasi jabatan publik, dan gangguan terhadap stabilitas kekuasaan eksekutif dalam sistem Presidensial. Purifikasi kewenangan seleksi pejabat publik di bidang eksekutif dapat dilakukan dengan menghapus ketentuan dalam undang-undang yang mengatur keterlibatan DPR dalam pengisian jabatan publik di bidang eksekutif. Dalam seleksi pejabat publik di bidang eksekutif, kontrol yang dapat dilakukan adalah melibatkan partisipasi publik secara substansial untuk memberikan tanggapan terhadap calon pejabat publik.